Neurological evaluation in quilombolas individuals exposed to organophosphorus pesticides in the brazilian Amazon population - LIMA, Izabelle Cristine Melo de (2023)
The aim of the present study was to investigate the relationship between the biochemical changes of this enzyme and the occurrence of neurological symptoms. In addition, an attempt is made to link the neurocognitive damage to environmental and human pollution near oil palm monocultures in the Amazon. This is a descriptive crosssectional study in a quilombola community in the state of Pará exposed to pesticides from 2017 to 2019 through epidemiological, clinical, biochemical, and toxicological investigations. Clinical, epidemiological, and laboratory data of the subjects were used for the study, as well as a neurological examination using a pesticide poisoning examination form from the Instituto Evandro Chagas. The sample of the study includes 195 people. Of these, more than half (54.9%) were male and the rest were female. As for the age group of the participants, 28.7% were children and adolescents, 58% of the subjects were between 20 and 59 years old, and another 13.3% were elderly. It was found that the reduced AChE levels were significantly lower in individuals with neurological complaints. In addition, the most frequently expressed signs and symptoms were weakness in 28.7%, memory impairment in another 24.6%, insomnia in 21%, and motor disorders in 15%. And it was found that the female gender manifested the neurological clinical picture the most and showed the greatest reduction in AChE enzyme. Therefore, it is necessary to biologically monitor populations exposed to the environment OP